Math, 14.05.2020snow01

Find the 20th term of the arithmetic sequence 17, 13, 9

Answers

The 20th term in the arithmetic sequence is -59.

17,13,9,5,1,-3,-7,-11,-15,-19,-23,-27,-31,-35,-39,-43,-47,-51,-55,-59

I hope my answers are correct.


1. Find the 16th term of the sequence 1, 5, 9, 13, ...

2. Find the 11th term of the arithmetic sequ
1. Find the 16th term of the sequence 1, 5, 9, 13, ...

2. Find the 11th term of the arithmetic sequ

answer:

13,14,15,16,17,18,19

Step-by-step explanation:

Start from 13 until you reach the number 19

answer for number 1:   :⊃

-59

Step-by-step explanation:

9-4 =5        5-4=1      1-4= -3        -3-4=-7     -7-4=-11        -11-4=-15         -15-4=-19      

-19-4=-23        -23-4=-27          -27-4=-31      -31-4=-35      -35-4=-39   -39-4=-43

-43 -4=-47      -47-4=-51           -51-4=-55       -55-4=-59

A20= -59

Step-by-step explanation:

Aⁿ= A¹ + (n-1) d

A20=17+(20-1)-4

=17+(19)-4

=17-76

A20= -59

9=17+(20-1)d

9=17+19d

17-9=19d

8 = 19d

19 19d (cancel 19)

0.42=d

Am i correct?

85

Step-by-step explanation:

9,13,17,21,25,28,33,37,41,45,49,53,57,61,65,69,73,77,81,85

-59

Step-by-step explanation:

-59 is the answer

Step-by-step explanation:

an=a1+(n-1)d

a20=17+(20-1)-4

a20=17+(-76)

a20=-59

an=a1+(n-1)d

a20=17+(20-1)-4

a20=17+(-76)

a20=59 is the answer.



Do you know the answer?

Other questions on the subject: Math

Math, 28.10.2019, nelspas422
to find the vertical asymptotes we solve the equation n(x) = 0. the vertical asymptotes are x = 1 and x = –1. to fund them solve the equation n(x) = 0. the numerator t(x) then the...Read More
1 more answers
Math, 29.10.2019, snow01
Composite figures. a  figure  (or  shape) that can be divided into more than one of the basic  figures  is said to be acomposite figure  (or  sha...Read More
1 more answers
Math, 31.10.2019, alexespinosa
in each box-there are 36 cans with radius 1.5 in and 6 in heightvcylinder=π[tex]r^{2} h[/tex]                 =π[tex](1.5)^{2} (6)[/t...Read More
3 more answers
Math, 14.11.2019, enrica11
  ( x^2/3 - y^1/3)³     ( x^2/3)³  -  3(x^2/3)² y^1/3  +  3x^2/3 (y^1/3)² - (y^1/3)³    x² - 3x^4/3 y^1/3 + 3x^2/3 y^2/3 - y...Read More
1 more answers